Questões técnicas em consultas com pais na psicanálise de crianças e adolescentes: uma visão winnicottiana - Brito, Claudia Vannozzi (2016)
Consultations with parents are extremely important to get a good result in the treatment of children and adolescents. This dissertation aims to study the technical issues involved, such as multiple transfers involving parents, analyst and patient and the management of the analytic setting. It also reflects on the various analyst positions in consultations with parents. For the research, it was used some vignettes of clinical cases attended in private practice. Donald Winnicott’s development theory is used to describe the importance of the environment for the mental health of children and adolescents. The therapeutic consultations he held with his patients formed the basis for the study and for the analysis of the need to open a space for parents. A space that serves to promote the health of both the child and its environment